2022
DOI: 10.1186/s12891-022-05435-1
|View full text |Cite
|
Sign up to set email alerts
|

Pain catastrophizing and associated factors in preoperative total knee arthroplasty in Lanzhou, China: a cross-sectional study

Abstract: Background Pain catastrophizing in preoperative total knee arthroplasty (TKA) patients is associated with several poorly characterised factors in the literature. This study investigated the current state and associated factors of preoperative pain catastrophizing in patients undergoing TKA. Methods This descriptive cross-sectional study was conducted at the orthopedics ward of two tertiary hospitals in Lanzhou, China. Pain catastrophizing was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Pain catastrophizing was assumed as a significant risk factor for TMDs and both subtypes according to univariate analysis, but its association with TMDs subtypes was not statistically significant after adjustment of demographic confounders. It was supposed that the perception of pain might be influenced by some demographic-social factors such as education level [ 48 , 49 ]. Therefore, the conclusion might differ in studies based on different cultural backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Pain catastrophizing was assumed as a significant risk factor for TMDs and both subtypes according to univariate analysis, but its association with TMDs subtypes was not statistically significant after adjustment of demographic confounders. It was supposed that the perception of pain might be influenced by some demographic-social factors such as education level [ 48 , 49 ]. Therefore, the conclusion might differ in studies based on different cultural backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…People with higher education levels might understand the questions better, or they may pay more attention to oral health issues. In addition, other studies have suggested that pain perception may be influenced by demographic‐social factors such as education level 40–42 . These are all possible causes of the above results.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, other studies have suggested that pain perception may be influenced by demographic-social factors such as education level. [40][41][42] These are all possible causes of the above results.…”
Section: Ta B L E 1 Descriptive Analyses Of the Datamentioning
confidence: 88%
“…A total score of ≥38 indicates a high degree of pain catastrophizing. 20 The Chinese version of the scale has demonstrated strong internal consistency, with Cronbach's α = 0.927. 19 Kinesiophobia was evaluated using the Chinese version of Tampa Scale of Kinesiophobia (TSK-11).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked to rate each item on a scale from 0 to 4, with options ranging from “never” to “always.” The total score on the scale ranges from 0 to 52. A total score of ≥38 indicates a high degree of pain catastrophizing 20 . The Chinese version of the scale has demonstrated strong internal consistency, with Cronbach's α = 0.927 19 …”
Section: Methodsmentioning
confidence: 99%